Employee Performance Effectiveness at the Office of the South Sulawesi Provincial General Election Supervisory Agency - Ramdani, Muhammad Hasyim; Darwis, Muh.; Saleh, Sirajuddin (ASHA Publishing, 2024)
Employee performance effectiveness is the ability of employees to do things correctly based on a goal plan that has been set. This study aims to determine the effectiveness of employee performance, supporting factors and inhibiting the effectiveness of employee performance at the South Sulawesi Provincial Bawaslu Office. Therefore, this study has a significant impact on employee performance that affects employee performance effectiveness. This research is qualitative, therefore to achieve the objectives of this research, the method of collecting data is by conducting observations, interviews, and documentation. The findings of this study show that all indicators used in this study can be categorized as effective. The indicator in question is that the quality of the work results of employees is effective because they receive coaching and are able to cooperate in completing the work. The quantity of work results is effective because employees are able to achieve targets and leaders are able to distribute tasks according to employee duties. Punctuality in completing tasks is effective because employees can complete tasks before the deadline. The presence of employees is still said to be less effective because there are employees who are still less disciplined and do not fulfill their obligations when working. The ability to cooperate with employees is effective because employees have the ability to communicate and complete work together. This study presents new information by associating detailed theories and research loci different from previous research on the effectiveness of employee performance so that it can be used as evaluation material for research loci to improve quality in the work environment.